A Comparative Analysis of Communicative Language Teaching (CLT) and Task-Based Language Teaching (TBLT) in Enhancing EFL Learners Outcomes - Muhammad Romdoni; Dimas Aulia Arzaqi; Triono Budi Nugroho; Muhammad Najmi Al Habsyi; Prananta Alvin Zikri; Zaitun Qamariah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
EFL learners need to have enough knowledge of english ability outcomes. This study explores the role of two prominent teaching methodologies Communicative Language Teaching (CLT) and Task-Based Language Teaching (TBLT) in enhancing English as a Foreign Language (EFL) learners' outcomes. English is essential for Indonesian students to access global knowledge, making effective teaching methodologies crucial for language acquisition. The study aims to compare CLT and TBLT, focusing on their contributions to developing EFL learners' discourse competence, communicative ability, and overall proficiency. Using a qualitative library research approach, this study reviews existing literature on both methodologies, examining their theoretical frameworks and classroom applications. The discussion highlights how CLT fosters communicative competence through real-life communication and how TBLT enhances language skills through task-based interactions. Both methods promote active participation, with CLT focusing on oral communication and TBLT on task completion. The study concludes that integrating both approaches can offer a comprehensive framework for optimizing EFL teaching practices, leading to improved language proficiency in diverse learning contexts.